Draft genome sequence of multidrug-resistant Citrobacter freundii MTR_GS_V1777 strain isolated from a spinach (Spinacia oleracea) sample in Gazipur, Bangladesh - Islam, Md. Saiful; Pramanik, Pritom Kumar; Rana, Md. Liton; Ramasamy, Srinivasan; Schreinemachers, Papijn; Oliva, Ricardo; Rahman, Md. Tanvir (American Society for Microbiology, 2024)
We announce a genome sequence of Citrobacter freundii MTR_GS_V1777 strain isolated from a vegetable sample in Bangladesh. This strain had a genome size of 4,997,753 bp (58.7× genome coverage) and contained two plasmids, typed as sequence type ST124, 38 predicted antibiotic resistance genes, and 77 predicted virulence factor genes.